Desigualdades socioespaciais e da acessibilidade promovida pelo transporte coletivo rodoviário : equidades em Belo Horizonte e no Vetor Norte metropolitano - Vanilson Cosme Oliveira Couto (2020)
This dissertation covers investigations about the relationship between accessibility promoted by the metropolitan public transport system, socioeconomic conditions and the availability of urban infrastructure. Since inequalities in the conditions of access to professional opportunities, studies, etc., lead to social exclusion and accentuate the vulnerability of population segments, a system of accessibility indicators and indices is proposed, which allows the identification of localities to be prioritized by public policies dedicated to suppress poverty and social exclusion. Using data from the 2010 population census and the 2012 Origin-Destination (OD) household survey, this system of indicators/indexes is applied to the municipality of Belo Horizonte (BH) and to some municipalities which composse the regional development vector commonly called “Metropolitan North Vector”. Feedback dynamics are detected, while socially vulnerable population segments settle in locations where urban infrastructure and accessibility are insufficiently provided and accentuate demands for more urban infrastructure and accessibility. The identification of these locations and the identification fo characteristics of the public transport system to be improved represent social contributions and the discrimination of accessibilty indicatos/indexes that allow measuring inequalities, as well equities, representes scientific contributions.